15
$\begingroup$

Stokes's theorem and the Gauss-Bonnet theorem are clearly very spiritually similar: they both relate the integral of a quantity $A$ over a region to the integral of some quantity $B$ over the boundary of the region, where $A$ can in some sense be thought of as a "curvature at one higher derivative" of $B$ or a closely related quantity. Is either of these theorems a special case of the other? If not, is there a more general theorem of which they are both special cases (which isn't too many levels higher up in abstraction)?

Edit: the answers to this follow-up question provide derivations of the Gauss-Bonnet theorem from Stokes's theorem in this paper, on pg. 105 of this textbook, and in Chapter 6 Section 1 of this textbook. Unfortunately, the derivations are too advanced for me to understand, as I haven't formally studied graduate-level differential geometry. I would appreciate any answer that summarizes the basic idea of the derivation.

$\endgroup$
  • $\begingroup$ this is a good question! $\endgroup$ – GiantTortoise1729 Sep 4 '16 at 7:16
  • 8
    $\begingroup$ Gauss Bonnet can be proved using Stokes theorem, but I cannot recall a way to prove Stokes using Gauss Bonnet. Indeed they are quite different: Stokes theorem consider only object in the smooth category while in Gauss Bonnet you consider object related to metric, curvatures... $\endgroup$ – user99914 Sep 4 '16 at 8:07
  • $\begingroup$ @JohnMa Thank you, that is a very insightful distinction. Could you very briefly outline the proof of the GB theorem from Stokes' theorem (like in one or two sentences with no equations)? $\endgroup$ – tparker Sep 4 '16 at 17:08
  • $\begingroup$ Good question, I'd like to know the answer. This might be related: mathoverflow.net/questions/50051/… $\endgroup$ – David Herrero Martí Oct 30 '16 at 1:08
1
$\begingroup$

I thought it would be nice to have a complete proof of the Gauss Bonnet formula, which is a great achivment of mathematics. Starting from the begining, I introduce the Pfaff forms and show the way they work. Then I use them to get the structure equations of the surface, the moving frame of the surface and the general curve on a surface. Combining all results I arive to $(8)$ which is a classical formula of differential geometry. With the help of $(8)$ I prove Liouville's formula and then the Gauss Bonnet formula. I make no use, or explain, the Levi-Civita theory, since it may be skiped and demands a lot of material to be taken into acount. I have also add some notes of mine and prove the fundamental theorem of Gauss and the equations of Mainardi and Godazzi.

Assume a two-dimesional surface $\textbf{S}$ of the Eucledean space $E_3\cong \textbf{R}^3$ which is of class $C^3$. That is, the surface is given by $$ \overline{x}=\overline{x}(u,v)=\{x_1(u,v),x_2(u,v),x_3(u,v)\}\textrm{, }u,v\in D $$ and $x_{i}(u,v)\in C^3$, $\overline{x}_u\times \overline{x}_v\neq \overline{0}$, $\overline{x}_u=\frac{\partial\overline{x}}{\partial u}$, $\overline{x}_v=\frac{\partial\overline{x}}{\partial v}$. In every point $P$ of the surface we attach a moving frame of three orthonormal vectors (that is $\{\overline{e}_1,\overline{e}_2,\overline{e}_3\}$ and $\left\langle \overline{e}_i,\overline{e}_j\right\rangle=\delta_{ij}$), with the assumption that $\overline{n}=\overline{e}_3$ is orthonormal to the tangent plane of surface (in every $P$).Then there exist Pfaff (differentiatable) forms, $\omega_i$ and $\omega_{ij}$ such that $$ d\overline{x}=\sum^{3}_{j=1}\omega_j\overline{e}_j\textrm{, }(\omega_3=0\Leftrightarrow \overline{n}=\overline{e}_3) $$ $$ d\overline{e}_i=\sum^{3}_{j=1}\omega_{ij}\overline{e}_j\textrm{, }i=1,2,3 $$ This can be seen as: $$ d\overline{x}=\{\partial_1 x_1du+\partial_2x_1dv,\partial_1 x_2du+\partial_2x_2dv,\partial_1 x_3du+\partial_2x_3dv\} $$ and the Pfaff derivatives $\nabla_kf$ and $\nabla_k\overline{F}$ for any function $f$ or vector $\overline{F}$ (resp.) are defined as $$ df=\sum^{3}_{k=1}(\nabla_kf)\omega_k=\sum^{3}_{k=1}\partial_kfdu_k.\tag 1 $$ Set now $$ q_1=\frac{d\omega_1}{\omega_1\wedge\omega_2}\textrm{, }q_2=\frac{d\omega_2}{\omega_1\wedge\omega_2}. $$ For to holds $(1)$ it must be $$ \nabla_1\nabla_2f-\nabla_2\nabla_1f+q_1\nabla_1f+q_2\nabla_2f=0\textrm{, (condition)}. $$ From the relations $d\left\langle\overline{e}_i,\overline{e}_j\right\rangle=0$, $d(d\overline{x})=\overline{0}$, $d(d\overline{n})=\overline{0}$, we get the structure equations of the surface: $$ \omega_{ij}+\omega_{ji}=0\textrm{, }i,j=1,2,3, $$ $$ d\omega_j=\sum^{3}_{i=1}\omega_i\wedge\omega_{ij}\textrm{, }j=1,2,3 $$ $$ d\omega_{ij}=\sum^{3}_{k=1}\omega_{ik}\wedge\omega_{kj}\textrm{, }i,j=1,2,3. $$ Observe that $\omega_3=\omega_{11}=\omega_{22}=\omega_{33}=0$ and we can write $$ d\overline{x}=\omega_1\overline{e}_1+\omega_2\overline{e}_2 $$ $$ d\overline{e}_1=\omega_{12}\overline{e}_2-\omega_{31}\overline{e}_3\tag 2 $$ $$ d\overline{e}_2=-\omega_{12}\overline{e}_1-\omega_{32}\overline{e}_3 $$ $$ d\overline{e}_3=\omega_{31}\overline{e}_1+\omega_{32}\overline{e}_2 $$ Moreover it is (structure equations): $$ d\omega_1=\omega_{12}\wedge\omega_2 $$ $$ d\omega_2=-\omega_{12}\wedge\omega_1 $$ $$ \omega_1\wedge\omega_{31}+\omega_2\wedge\omega_{32}=0 $$ $$ d\omega_{12}=-\omega_{31}\wedge\omega_{32}\tag 3 $$ $$ d\omega_{31}=\omega_{12}\wedge\omega_{32} $$ $$ d\omega_{32}=-\omega_{12}\wedge\omega_{31} $$ If we write the connections (of $\omega_{ij}$ in terms of $\omega_i$): $$ \omega_{12}=\xi\omega_1+\zeta \omega_2 $$ $$ \omega_{31}=-a\omega_1-b\omega_2 $$ $$ \omega_{32}=\eta\omega_1-c\omega_2 $$ We easily get (from the structure equations) $\xi=q_1$, $\zeta=q_2$, $\eta=-b$. Hence $$ \omega_{12}=q_1\omega_1+q_2 \omega_2\tag 4 $$ $$ \omega_{31}=-a\omega_1-b\omega_2\tag 5 $$ $$ \omega_{32}=-b\omega_1-c\omega_2.\tag 6 $$

Assume now a ''strange'' operator $\theta$ such that $$ \theta(A,B)=\left| \begin{array}{cc} \nabla_1\textrm{ }\nabla_2\\ A\textrm{ }B \end{array} \right|+q_1A+q_2B=\nabla_1B-\nabla_2A+q_1A+q_2B. $$ This is not so ''strange'' since if $\omega=A\omega_1+B\omega_2$ and $f$ function of $u,v$, then $$ d(f\omega)=\theta(Af,Bf)\omega_1\wedge\omega_2=\left(\left| \begin{array}{cc} \nabla_1f\textrm{ }\nabla_2f\\ A\textrm{ }B \end{array} \right|+\theta(A,B)f\right)\omega_1\wedge\omega_2. $$ By this way we have $$ d\omega_{12}=\theta(q_1,q_2)\omega_1\wedge\omega_2=-K\omega_1\wedge\omega_2\textrm{, }K=ac-b^2\textrm{, (Gauss curvature)} $$ $$ d\omega_{31}=\theta(-a,-b)\omega_1\wedge\omega_2=(q_2b-q_1c)\omega_1\wedge\omega_2=\frac{q_2b-q_1c}{K}\omega_{31}\wedge\omega_{32} $$ and $$ d\omega_{31}=q^{III}_1\omega_{31}\wedge\omega_{32} $$ $$ d\omega_{32}=q^{III}_2\omega_{31}\wedge\omega_{32} $$ Hence the theorem of Gauss is: $$ \theta(q_1,q_2)=-K=b^2-ac. $$ The Mainardi and Godazzi equations are: $$ \theta(a,b)=\left| \begin{array}{cc} q_1\textrm{ }q_2\\ a\textrm{ }b \end{array} \right| $$ $$ \theta(b,c)=\left| \begin{array}{cc} q_1\textrm{ }q_2\\ b\textrm{ }c \end{array} \right|. $$ The condition of Pfaff derivatrives becomes $$ \theta(\nabla_1f,\nabla_2f)=0 $$ and the Beltrami derivative is $$ \Delta_2f=\theta(-\nabla_2f,\nabla_1f) $$ $$ \theta(\overline{e}_1,\overline{e}_2)=0. $$ ... etc

Now assume a curve $\Gamma$ on the surface and its moving frame in $P\in\textbf{S}$ as follows: $\overline{t}$ is tangent of the curve in $P$, $\overline{n}$ is orthonormal of the surface in $P$ and $\overline{n}_g$ is orthonormal both in $\overline{t}$ and $\overline{n}$. Then we can easily see that exists $\frac{1}{\rho_g}$,$\frac{1}{R}$ and $\frac{1}{\tau_g}$ such that $$ \frac{d\overline{t}}{ds}=\frac{\overline{n}_g}{\rho_g}+\frac{\overline{n}}{R}\tag 7 $$ $$ \frac{d\overline{n}_g}{ds}=-\frac{\overline{t}}{\rho_g}+\frac{\overline{n}}{\tau_g} $$ $$ \frac{d\overline{n}}{ds}=-\frac{\overline{t}}{R}-\frac{\overline{n}_g}{\tau_g}. $$ Where $s$ being the natural parameter of $\Gamma$. All $\frac{1}{\rho_g}$,$\frac{1}{R}$,$\frac{1}{\tau_g}$ are invariants. If we consider also the Frenet frame $\{\overline{t},\overline{h},\overline{b}\}$, which is such $$ \frac{d\overline{t}}{ds}=\frac{h}{\rho} $$ $$ \frac{d\overline{h}}{ds}=-\frac{\overline{t}}{\rho}+\frac{\overline{b}}{\tau} $$ $$ \frac{d\overline{b}}{ds}=-\frac{\overline{h}}{\tau} $$ and take the angle $\psi$ between $\overline{h}$ and $\overline{n}$, we get $(\psi\in[0,2\pi))$ $$ \frac{1}{\rho_g}=\frac{\sin(\psi)}{\rho} $$ $$ \frac{1}{R}=\frac{\cos(\psi)}{\rho} $$ $$ \frac{1}{\tau_g}=\frac{1}{\tau}+\frac{d\psi}{ds}. $$

Gauss consider first the geodesic curvature $\frac{1}{\rho_g}$ of a curve in a surface. From (7) we have $$ \frac{1}{\rho_g}=\left\langle\frac{d\overline{t}}{ds},\overline{n}_g\right\rangle. $$ Also $ \overline{t}=\frac{d\overline{x}}{ds}\textrm{, }\frac{d\overline{t}}{ds}=\frac{d^2\overline{x}}{ds^2}\textrm{, }n_g=\overline{n}\times \overline{t}$ and $$ \frac{1}{\rho_g}=\left(\frac{d\overline{x}}{ds},\frac{d^2\overline{x}}{ds^2},\overline{n}\right)=\textrm{det}\left(\frac{d\overline{x}}{ds},\frac{d^2\overline{x}}{ds^2},\overline{n}\right)\tag 8 $$ Assuume now the surface curve coresponding to $\omega_2=0$ and we ask about its geodesic curvature. We have $$ d\overline{x}=\omega_1\overline{e}_1+\omega_2\overline{e}_2\Rightarrow \left(\frac{d\overline{x}}{ds}\right)_{\omega_2=0}=\frac{\omega_1}{ds}\overline{e}_1. $$ From (2) we get $$ \left(\frac{d^2\overline{x}}{ds^2}\right)_{\omega_2=0}=\frac{d}{ds}\left(\frac{\omega_1}{ds}\right)\overline{e}_1+\frac{\omega_1\omega_{12}}{ds^2}\overline{e}_2-\frac{\omega_1\omega_{31}}{ds^2}\overline{e}_3 $$ From (2) and (8) we find $$ \left(\frac{1}{\rho_g}\right)_{\omega_2=0}=q_1. $$ In the same manner for the curve $\omega_1=0$: $$ \left(\frac{1}{\rho_g}\right)_{\omega_1=0}=q_2 $$ Assume now a curve $\Gamma$ on a surface. Let $\overline{t}$ be its tangent vector and $\phi$ is the angle between $\overline{t}$ and $\overline{e}_1$ (the tangent $\overline{t}$ is on the $\{\overline{e}_1,\overline{e}_2\}$ plane).

We have $$ \left(\frac{d\overline{x}}{ds}\right)_{\Gamma}=\overline{t}=\cos(\phi)\overline{e}_1+\sin(\phi)\overline{e}_2 $$ and $$ \left(\frac{d^2\overline{x}}{ds^2}\right)_{\Gamma}=\frac{\omega_{12}+d\phi}{ds}(-\sin(\phi)\overline{e}_1+\cos(\phi)\overline{e}_2)-\frac{\omega_{31}\cos(\phi)+\omega_{32}\sin(\phi)}{ds}\overline{e}_3 $$ From relation (8) we get $$ \frac{1}{\rho_g}=\frac{d\phi}{ds}+\frac{\omega_{12}}{ds}=\frac{d\phi}{ds}+q_1\frac{\omega_1}{ds}+q_2\frac{\omega_2}{ds}. $$ But $\cos(\phi)=\frac{\omega_1}{ds}$, $\sin(\phi)=\frac{\omega_2}{ds}$. Hence we find $$ \frac{1}{\rho_g}=\frac{d\phi}{ds}+q_1\cos(\phi)+q_2\sin(\phi)\textrm{, Liouville formula}. $$ or in $\theta$ notation $$ \frac{1}{\rho_g}=\theta(\cos(\phi),\sin(\phi)). $$

Proof of the Gauss Bonnet Formula

From the formulas $$ \frac{1}{\rho_g}=\frac{\omega_{12}}{ds}+\frac{d\phi}{ds}, $$ $$ d\omega_{12}=-\omega_{31}\wedge\omega_{32}=-K\omega_1\wedge\omega_2 $$ and Stokes theorem we get: $$ \int_{\partial D}\frac{ds}{\rho_g}=\int_{\partial D}\omega_{12}+\int_{\partial D}\frac{d\phi}{ds}ds=\int\int_{D}d(\omega_{12})+\int_{\partial D}d\phi= $$ $$ =-\int\int_{D}\frac{\omega_{31}\wedge\omega_{32}}{\omega_1\wedge\omega_2}\omega_1\wedge\omega_2+\int_{\partial D}d\phi=-\int\int_{D}K\omega_1\wedge\omega_2+2\pi, $$ since $$ \int_{\partial_D}d\phi=2\pi. $$ Hence we get the Gauss Bonnet formula $$ \int_{\partial D}\frac{ds}{\rho_g}+\int\int_{D}K\omega_1\wedge\omega_2=2\pi. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.